CINEMA in Linguistic Worldview of Russian North Villagers - E. N. Ilyina (Научный диалог, 2022)
Folk ideas about cinematic art and cinematography are studied. The recordings of the speech of the inhabitants of the Vologda Territory, made by the author of the article in the period from 1988 to 2021, as well as citation material recorded in the published issues and card file of the Dictionary of Vologda Dialects, are analyzed. A relatively late entry of cinema into the everyday life of the northern village is established (late 60s — 70s of the XX century). The priority of human biological survival in difficult natural conditions determines the attitude towards cinema as a form of spending free time in accordance with the routine of daily and calendar peasant work. The device of the village society serves as a kind of “filter” for the perception of the plotthematic, character and aesthetic components of cinema: the rural viewer perceives the sphere of cinema as bright and attractive, but nevertheless redundant for village life and unsafe for public morality. Only that which is within the circle of interests of the peasant, that is of value or anti-value for him, is verbalized. The traditional nature of the dialectal picture of the world is manifested, on the one hand, in the desire to enter a new form of “urban culture” into the circle of rural entertainment, and on the other hand, in the use of well-established lexical and phraseological means and genre forms in the practice of discussing the subject, axiological and actional components of the cinema sphere.